Measuring What Counts in Life: The Development and Initial Validation of the Fulfilled Life Scale (FLS) - Baumann, Doris; Ruch, Willibald (Frontiers in Psychology, 2022)
In a recent work, we introduced a theoretical model for fulfillment in life that covers cognitive and affective components and distinguishes different time frames. The present study evaluates this model and describes the construction of the Fulfilled Life Scale (FLS) to assess fulfillment regarding the whole lived life retrospectively. We investigated the scale in two samples (Sample 1: N = 282 adults aged 50–93 years; Sample 2: N = 406 adults aged 40–85 years). The model of the cognitive component combines three sources of fulfillment (self, life, impact/legacy) with three criteria (wholeness, fit, value), yielding nine facets. Employing hierarchical factor analysis, we inspected all solutions between one and nine. We identified three optimal factors, which we labeled unfolded self and life, the worthwhile life, and positive impact and legacy. Next, we selected marker items and replicated the factor structure in Sample 2. The three scales were positively intercorrelated and showed good internal consistency in both samples. For the affective component, exploratory and confirmatory factor analyses established a one-factor structure in both samples, and high internal consistency was obtained. Across a range of related constructs, we demonstrated construct and criterion validity. Notably, cognitive and affective fulfillment incrementally predicted a global rating of a fulfilled life and mental well-being, even after controlling for subjective and eudaimonic well-being. Overall, the study proves that the FLS is necessary to capture people’s experience of a fulfilled life, which could not be assessed sufficiently with previous well-being measures. Both cognitive and affective fulfillment were able to predict additional variance in mental well-being. Moreover, the study reveals psychometric support for the FLS and presents the first evidence on its validity. Lastly, applications in research and practice are discussed, especially in the context of living and aging well in the second half of life.